2018
DOI: 10.1111/apa.14517
|View full text |Cite
|
Sign up to set email alerts
|

Children and adolescents with phenylketonuria display fluctuations in their blood phenylalanine levels

Abstract: The blood phenylalanine levels of patients with mild PKU showed minor interindividual differences, which may have allowed fluctuations to exert a negative effect on the FSIQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…A review of the literature suggests that it is the cumulative effect of day-to-day fluctuations over months and years that may affect cognition impacting on intelligence quotients [25,26]. A recent short study over 26 weeks by Feldmann concluded that Phe fluctuations were negatively correlated with IQ in children with mild PKU [27]. Although no study has definitively shown that fluctuation in Phe affects neurocognitive outcome, evidence suggests there is a correlation, and therefore the stabilization of Phe concentrations should be the aim of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature suggests that it is the cumulative effect of day-to-day fluctuations over months and years that may affect cognition impacting on intelligence quotients [25,26]. A recent short study over 26 weeks by Feldmann concluded that Phe fluctuations were negatively correlated with IQ in children with mild PKU [27]. Although no study has definitively shown that fluctuation in Phe affects neurocognitive outcome, evidence suggests there is a correlation, and therefore the stabilization of Phe concentrations should be the aim of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors highlight the variability in Phe levels as a stronger predictor of cognitive performance in ETPKU patients than the yearly median of blood Phe levels [22,26]. This impact of Phe levels fluctuations could be even especially meaningful for m-PKU patients [27]. Finally, our sample size remained limited to 39 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Feldman et al (2019) found that persons with early treated PAH deficiency developed an IQ within the normal range, but still had lower IQ scores than their unaffected counterparts. Feldman et al (2018) found in patients with mild PAH deficiency, that full scale IQ was negatively correlated with fluctuating Phe levels; for patients with classical PKU, the opposite was true.…”
Section: Neurocognitive Complicationsmentioning
confidence: 99%